THU0452 Psoriatic Arthritis and Psoriasis: The Ongoing Need for A Multidisciplinary Approach To Management. (15th July 2016) - McCusker, S.; Leman, J.; Bawa, S.; Gordon, M.-M.
Abstract : Background: Psoriasis is a common inflammatory condition of the skin, associated with significant morbidity. Around 20% of patients with psoriasis suffer from psoriatic arthritis (PsA) (1). SIGN guidelines recommend a multidisciplinary approach in the assessment and management of patients with PsA or psoriasis. There is currently a combined clinic in Glasgow for review of patients with severe psoriasis and PsA, whilst most patients continue to attend separate dermatologist or rheumatologist led clinics. Objectives: To review the population groups attending separate dermatologist and rheumatologist led clinics, to establish adherence to SIGN guidelines with regards to management, and to gauge the potential unmet demand for patients who may benefit from review in a combined clinic. Methods: All patients attending tertiary PsA or psoriasis clinics in March 2015 were invited to complete a questionnaire on their disease, demographics and clinic attendance. Patients attending the PsA clinic completed a DLQI (Dermatology Life Quality Index), those attending the psoriasis clinic completed a PEST (Psoriasis Epidemiology Screening Tool) score. Results: 48 patients attending the PsA clinic and 34 patients attending the psoriasis clinic were included (n=82). 63% (n=52) had both PsA and psoriasis. 14 (17%) patients saw their GP for annual review. 38% (n=18) and 21% (n=10) of patients attending the PsA clinic had been offered referral to physiotherapy and occupational therapy respectively. 22 (42%) of the 52 patients with psoriasis and PsA attended both rheumatology and dermatology, with 4% (n=3) attending the combined clinic (chart 1). 87% (n=45) of patients with a diagnosis of both psoriasis and PsA would find a combined clinic useful. A PEST score of ≥3 is considered positive, and referral to a rheumatologist is recommended (1). 50% of patients attending the psoriasis clinic had a PEST score ≥3. 59% of these patients had been referred to, or were currently attending, a rheumatology clinic. 10 patients attending the PsA clinic had a DLQI ≥6, these patients should be referred to a dermatologist (1). 60% of these patients had seen a dermatologist. Leflunomide is the recommended systemic drug of choice in patients with PsA. 1 patient in the PsA group was receiving leflunomide. Methotrexate was the most commonly used systemic therapy in 20 patients in the PsA group and 6 patients in the psoriasis group. Adalimumab was the most commonly used biologic in both groups (n=17). Conclusions: Currently there are multiple rheumatology and dermatology clinics for the management of PsA and psoriasis throughout Greater Glasgow and Clyde, with only one combined clinic. Despite clear recommendations for a multidisciplinary approach to the management of psoriasis and PsA, only 4% of our patients attend a combined clinic, fewer than a third have been reviewed by a physiotherapist or occupational therapist and only 17% have an annual GP review. 41% of patients attending the psoriasis clinic with a positive PEST score had not seen a rheumatologist while 40% of patients with a DLQI ≥6 attending the PsA clinic had not seen a dermatologist. This audit suggests the need to consider greater access to combined clinics, to allow a multidisciplinary approach to management. References: SIGN Guideline 121, Diagnosis and management of psoriasis and psoriatic arthritis in adults; a national clinical guideline, Oct 2010 Disclosure of Interest: None declared